Understanding Nurture’s Influence on the Development of Mental Disorders (Translation: The University of Toledo Journal of Medical Sciences, 2025)
The grand question of Nature (genes and DNA) versus Nurture (environment, parenting) has been debated for a long time. In the passage above, it shows that psychiatrists used to think that schizophrenia was caused by “bad” mothering. If generalized, one might conclude that any or all mental disorders may be caused by “nurture.” In class, so far, you have seen three different patients with three different disorders (depression, schizophrenia, and addiction). Choose either “nature” or “nurture” as your stance and write an essay persuading the reader that one is more important than the other in terms of causing mental illness. Using examples from the passage above, class interviews, optional reading, and/or your own experiences would be much appreciated!
Keywords: NSCI1000